Project conducted in Hirakata to improve cervical cancer screening rates in 20‐year‐old Japanese: Influencing parents to recommend that their daughters undergo cervical cancer screening. Issue 12 (19th September 2016) - Yagi, Asami; Ueda, Yutaka; Egawa‐Takata, Tomomi; Tanaka, Yusuke; Terai, Yoshito; Ohmichi, Masahide; Ichimura, Tomoyuki; Sumi, Toshiyuki; Murata, Hiromi; Okada, Hidetaka; Nakai, Hidekatsu; Mandai, Masaki; et al.
Abstract: Aim: In Japan, the rate of routine cervical cancer screening is quite low, and the incidence of cervical cancer has recently been increasing. Our objective was to investigate ways to effectively influence parental willingness to recommend that their 20‐year‐old daughters undergo cervical cancer screening. Methods: We targeted parents whose 20‐year‐old daughters were living with them. In fiscal year 2013, as usual, the daughter received a reminder postcard several months after they had received a free coupon for cervical cancer screening. In fiscal year 2014, the targeted parents received a cervical cancer information leaflet, as well as a cartoon about cervical cancer to show to their daughters, with a request that they recommend to their daughter that she undergo cervical cancer screening. The subsequent screening rates for fiscal years 2013 and 2014 were compared. Results: The cervical cancer screening rate of 20‐year‐old women whose parents received the information packet in fiscal year 2014 was significantly higher than for the women who, in fiscal year 2013, received only a simple reminder postcard ( P < 0.001). As a result, the total screening rate for 20‐year‐old women for the whole of the 2014 fiscal year was significantly increased over 2013 ( P < 0.001). Conclusion: For the first time, we have shown that the parents of 20‐year‐old daughters can be motivated to recommend that their daughters receive their first cervical cancer screening. This was achieved by sending a cervical cancer information leaflet and a cartoon about cervical cancer for these parents to show to their daughters. This method was significantly effective for improving cervical cancer screening rates.